Self-medication practices and their characteristics among Iranian university students - Rohaneh Rahimisadegh; Nader Sharifi; Vahid Kohpeima Jahromi; Razieh Zahedi; Zahra Rostayee; Razieh Asadi (BMC, 2022)
Abstract Background Self-medication in students, as educated people, is one of the most important health issues. It is known that inappropriate self-medication is harmful for individuals as it has potential risks, disrupts the drug market and increases the per capita financial drug consumption. Thus, the aim of this study is to investigate the habits related to drug use and the prevalence of self-medication practices among university students. Methods This cross-sectional study was conducted in 2021 at Jahrom universities/Iran, using an electronic "self-medication practices and medication habits" questionnaire. A total of 848 students from four healthcare and non-healthcare universities participated in the study. Results The prevalence of self-medication among students was 44.8%. The most common medicines used for self-medication included cold remedies and sedatives that were used by 33% of the students. About 47% of students stated that they have used antibiotics without a physician's prescription. The internet and social networks were the source of information on self-medication in about 40% of students. There was no significant difference in self-medication between medical and non-medical students (OR = 0.865, 95% CI: 0.659-1.134). Self-medication in students with underlying disease was higher than students without underlying disease (OR = 2.8, 95% CI: 1.39-5.60). Conclusions Self-medication had a high prevalence among students. The best strategy to reduce or eliminate self-medication is to raise students' awareness and knowledge about potential risk of self-medication practices.